Acute upper limb compartment syndrome in children: special focus on nerve recovery. Issue 3 (29th October 2020) - Jerome, Terrence Jose
Abstract : Background: Many studies have discussed acute compartment syndrome in children associated with or without fractures and have given their visible perspectives. Little is known about the nerve involvement and the factors associated with recovery patterns in these patients. We intend to propose that ischemic nerve and muscles tend to regenerate after surgical decompression but in a different pattern and the given circumstances. Methods: Twenty-four children with acute compartment syndrome in the upper limb were analyzed between 2009 and 2015. Data included demographic features of these patients, the time interval between the injury and surgery, and the attempt to correlate with motor and sensory recovery. Results: The average follow-up was 67.3 months (range 59–80). Of the 24, 14 patients (58%) had immediate recovery of motor and sensory functions. The remaining 10 patients had variable recovery patterns with a mean time for the radial nerve, median nerve and ulnar nerve motor recovery of 6.0, 7.5 and 8.5 months, respectively, and sensory recovery at 12, 12 and 13 months, respectively. The overall study had a mean sensory recovery as per the Medical Research Council (MRC) of S3 in 3 (12%) and S4 in 21 (88%). The mean 2-point discrimination (2PD) was 6.9 mm (range 5–10). Twenty-one patients (88%) had a full range of movements at their final follow-up with a mean Visual Analog Scale score of 0.6; a quick Disabilities of the Arm, Shoulder and Hand score of 5.9 (range 2.3–25.0) and a Mayo wrist score of 79. Conclusions: There was a definite motor and sensory recovery in patients who underwent surgical decompression in acute compartment syndrome of the upper limb irrespective of age, gender, delay in presentation and various etiologies. The motor and nerve fibers can regenerate after ischemic sequela of compartment syndrome.